Paper-based inoculum of Bacillus megaterium and its practical application for simple culture preparation - Kanjanamaneesathian, Mana; Nimanong, Wasunan (New Zealand Plant Protection, 2019)
The bacterium Bacillus megaterium can be used to biologically control sheath blight and grain discoloration in rice. Large-scale inoculations using liquid cultures are cumbersome so the efficacy of an alternative, paper-based system was examined. Bacterial endospores were embedded on filter papers and multiplied using a simple culture technique. The resulting suspension was used to pre-soak yardlong bean and cucumber seeds before sowing to assess its effect on seed germination and weight. The efficacy of the bacterium in protecting cucumber seeds from pre-emergent damping-off was also examined. The population of bacteria embedded in paper declined initially but remained stable for 150 days at room temperature. Bacterial culture reduced seed germination of cucumber and seedling weight of yardlong beans. Dilution with water either increased or reduced germination of cucumber seeds depending on concentration. A 1:10 v/v dilution increased cucumber-seed germination in a pre-emergent damping-off pot test but all seedlings later died, irrespective of treatment. Paper-based inoculum has the potential to replace liquid inoculum but further work is required to optimise the concentrations of the bacterial culture to achieve disease control without adversely affecting the host plant.